2006
DOI: 10.1177/1043454206287301
|View full text |Cite
|
Sign up to set email alerts
|

Personal Web Home Pages of Adolescents With Cancer: Self-Presentation, Information Dissemination, and Interpersonal Connection

Abstract: The content of personal Web home pages created by adolescents with cancer is a new source of information about this population of potential benefit to oncology nurses and psychologists. Individual Internet elements found on 21 home pages created by youths with cancer (14-22 years old) were rated for cancer-related self-presentation, information dissemination, and interpersonal connection. Examples of adolescents' online narratives were also recorded. Adolescents with cancer used various Internet elements on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…This may be attributable to the high degree of anonymity that exists in a non-threatening environment which can encourage honest communication and empathy with peers. Suzuki and Beale (2006) noted that teenagers who had created their own webpages were comfortable discussing personal experiences openly via diary entries, personal essays or even poetry.…”
Section: Online Data Collection 351 Justification For Use Of Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributable to the high degree of anonymity that exists in a non-threatening environment which can encourage honest communication and empathy with peers. Suzuki and Beale (2006) noted that teenagers who had created their own webpages were comfortable discussing personal experiences openly via diary entries, personal essays or even poetry.…”
Section: Online Data Collection 351 Justification For Use Of Onlinementioning
confidence: 99%
“…The authors noticed that the sites were providing important information and emotional support for individuals (Suzuki and Beale, 2006). Similarly, Valaitis and Sword (2005) found that a website originally set up to gather the views of pregnant and parenting teens evolved into a support tool for the young people, who reported that they felt less isolated and had more friends as a result of using it.…”
Section: Online Data Collection 351 Justification For Use Of Onlinementioning
confidence: 99%
“…Patients with cancer have embraced personal Web pages as another means of communicating information to and receiving support from their social networks (Suzuki & Beale, 2006). Some organizations (e.g., CaringBridge ® , Carepages) offer free, personalized, password-protected Web sites to patients that provide an easy, accessible, and private way to share information and receive support in a controlled manner (Chandler, 2006).…”
Section: Communication Optionsmentioning
confidence: 99%
“…Developments in information and communication technologies have opened up new possibilities in the field of health care (Suzuki and Calzo, 2004;Suzuki and Beale, 2006). This includes the opportunity to monitor patients at home and provide 'real-time' information to health care providers and, in turn, prompt timely support.…”
Section: Introductionmentioning
confidence: 99%